Implemented occupational health surveillance limits the spread of SARS-CoV-2 Omicron at the workplace - Gesto, João Silveira Moledo; Cabanelas, Adriana; Farjun, Bruna; dos Santos, Monique Cristina; Fidalgo-Neto, Antonio A.; Kuriyama, Sergio N.; Souza, Thiago Moreno L. (Frontiers in Medicine, 2022)
The global spread of the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) has put an enormous pressure on human societies, at both health and economic levels. Early diagnosis of SARS-CoV-2, the causative agent of 2019 coronavirus disease (COVID-19), has proved an efficient method to rapidly isolate positive individuals and reduce transmission rates, thus alleviating its negative impact on societies’ well-being and economic growth. In this work, through a coordinated and centralized effort to monitor SARS-CoV-2 circulation in companies from the State of Rio de Janeiro, Brazil, we have detected and linked an early rise of infection rates in January 2022 to the introduction of the Omicron variant of concern (VoC) (BA.1). Interestingly, when the Omicron genomic isolates were compared to correlates from public datasets, it was revealed that introduction events were multiple, with possible migration routes mapping to: Mali; Oman and USA; and Italy, Latin America and USA. In addition, we have built a haplotype network with our genomic dataset and found no strong evidence of transmission chains, between and within companies. Considering Omicron’s particularly high transmissibility, and that most of our samples (> 87%) arose from 3 out of 10 companies, these findings suggest that workers from such environments were exposed to SARS-CoV-2 outside their company boundaries. Thus, using a mixed strategy in which quick molecular diagnosis finds support in comprehensive genomic analysis, we have shown that a successfully implemented occupational health program should contribute to document emerging VoC to limit the spread of SARS-CoV-2 at the workplace.